Assessment of toxic and carcinogenic elements in Dust and Soil in Baghdad city and their effects on the distribution of some diseases - Sultan, Maitham; Al-Rubaiee, Mahdi; Abdulrahim, Esam (Iraqi Journal of Science, 2024)
The studies conducted by the Center for the Study of War in New York gave firmly evidence beyond doubt, is that the dust particles, which gathered in the desert of Kuwait and Iraq have a link to what happened to members of the military forces of disorder in the nerves and appeared to them of the symptoms of cancer and disorders of the respiratory system and heart disease. The dust particles (sand) in Kuwait and Iraq contain toxic substances, which dates back to the pollution caused by military equipment and dismantle the desert sands and turn it into light dust.The aim of this research to determination some toxic and carcenoginc elements such as (Pb, Co, Ni, Cu, Zn, Fe and Cd) in dust and soil in Baghdad city and their health effects types of resulting diseases. Samples were collected from airborne stations in the study area during the dusty days, also accompanied the process modeling dust collecting surface soil samples for the same selected sites in the city of Baghdad, and then the analysis is performed for the purpose of determining the concentrations of toxic and carcinogenic elements and compare it with the global determinants.Search Results showed that there is a large increase Total suspended particles (TSP) concentrations in all sites compared with allowable limits, where the highest concentration in the Al-Ealam site (2241.37μg/m3), and the lowest was in the Al-ameryah site (1096.04 μg/m3) which is much higher than the permissible limits. It also found that most concentrations of chemical toxic elements in the dust did not exceed the permissible limits, except concentrations of zinc and iron has exceeded the permissible limits, where the highest concentration of zinc in the highway New Baghdad – AlDorah (10.63ppm) is higher than the permissible limits. The highest concentration of iron in Al-Jadiryah (ministry of science and technology) (8.56ppm). Through the research found that dust storms and strong winds blowing in the soil is an important factor in the increase TSP and some toxic elements concentrations in the air, and the movement of vehicles can play an important role in increasing concentrations of TSP in the atmosphere as a result of movement that lead to volatility dust, as well as the TSP emitted from car exhausts, in addition to Industrial Activities especially brick factories and power plants, which could affect the concentrations of these elements in the soil of same selected sites. The results also show that most concentrations of heavy metals in the soil of the selected sites did not exceed the permissible limits except zinc and nickel, has reached the highest concentration of zinc in the Al-Amiryah and Al-Ealam sites the highest of the standards limits, and is due to the effect of divorced some industrial activities and the impact of some divorced vehicles and others.